2014
DOI: 10.1016/j.pec.2013.12.020
|View full text |Cite
|
Sign up to set email alerts
|

Healthcare providers’ awareness of the information needs of their cardiac rehabilitation patients throughout the program continuum

Abstract: These findings could inform evaluation and improvement of CR education programming, to ensure programs are meeting patient information needs across all stages of recovery.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
20
0
2

Year Published

2015
2015
2025
2025

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 41 publications
(22 citation statements)
references
References 35 publications
0
20
0
2
Order By: Relevance
“…Patients desired less information on their pathology and on how to self-manage it, whereas they continued to desire medical information related to medical treatment and complications of the disease. This preference for medical information compared with lifestyle information has been identified in previous research [21,22,[33][34][35][36] and deserves attention by health practitioners. Research continuously shows that patients fail to adhere correctly to medical advice or to change their unhealthy behaviors [37][38][39]; thus, it is essential to help them understand what they can do to self-manage their health condition and to prevent complications.…”
Section: Discussionmentioning
confidence: 59%
See 1 more Smart Citation
“…Patients desired less information on their pathology and on how to self-manage it, whereas they continued to desire medical information related to medical treatment and complications of the disease. This preference for medical information compared with lifestyle information has been identified in previous research [21,22,[33][34][35][36] and deserves attention by health practitioners. Research continuously shows that patients fail to adhere correctly to medical advice or to change their unhealthy behaviors [37][38][39]; thus, it is essential to help them understand what they can do to self-manage their health condition and to prevent complications.…”
Section: Discussionmentioning
confidence: 59%
“…Research in this field found that patients with acute coronary syndrome, myocardial infarction, and heart failure judge all types of information as important, with a preference for information on medication (names, dosage and side effects), risk factors (especially how to modify incorrect behaviors), and physiology (knowing how to manage signs and symptoms) [18][19][20][21]. However, the majority of researches has been conducted using a crosssectional methodology; few studies have been conducted using a longitudinal approach and there is still a lack of knowledge about how the specific need for health information changes as the disease progresses.…”
Section: Introductionmentioning
confidence: 99%
“…It serves as a significant part of disease management and secondary prevention, which can help patients understand the therapies and comply with the recommended health behaviors 11,12. Findings from recent studies presented the benefits of patient education in improving self-management abilities and quality of life while reducing healthcare costs 12,13…”
Section: Introductionmentioning
confidence: 99%
“…One recent study has been conducted with the aim of investigating how patients’ information needs change over the course of a six-month long cardiac rehabilitation program, but it is still a cross-sectional study. It found that patients were significantly more interested in information about emergency/safety at the beginning of the program, while information about general/social concern and risk factors was preferred at the middle [ 25 ]. However, the adoption of a cross-sectional design is not appropriate for studying change over time.…”
Section: Introductionmentioning
confidence: 99%